Efficacy of Brain Gym on the Cognitive Function Improvement of People with Dementia - Fery Agusman Motuho Mendrofa; Dwi Indah Iswanti; Umi Hani (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Dementia is a neurodegenerative syndrome caused by a chronic and progressive disorder accompanied by decreased brain function that affects emotions, memory, decision making, behavior and other brain functions that interfere with daily activities. This study aimed to determine differences in cognitive function in elderly dementia before and after brain exercise. This was a quasi-experimental research with one group pre and post-test design conducted in June 2020. The population was residents in some nursing homes in Semarang City. Samples who were willing to participate in research, 60-80 years old, and had Clock Drawing Test score in more than 2 were included for this study. The sample in this study was 63 older adults who were selected using a purposive sampling technique. The respondents enrolled in brain gym eight times each morning for 10-15 minutes in 2 weeks. Due to the pandemic, these interventions assisted by facilitators and adhered to health protocols in every interaction. The cognitive function obtained from the Short Portable Mental Status Questionnaire for pre and post-test. Univariate analysis described cognitive function in the elderly before and after brain exercise. The normality test using Shapiro Wilk showed that the data were normally distributed so that the dependent T-test was carried out to determine the effectiveness of brain exercise therapy on cognitive function in elderly dementia. The mean cognitive function before brain exercise was 6.6, and after brain exercise, it was 8.8. There was a significant difference between cognitive function before and after brain exercise (p-value <o.o5). Brain exercise affects improving cognitive function in older adults with dementia.